(untitled) (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Background: Cacalia hastata L. is used in Mongolian traditional medicine to treat wounds, reduce fever, treat gastric ulcers, and expel bile. In addition, Cacalia hastata L. is determined to have antiinflammation and antibacterial and antiviral activities. In this study, we determined the antioxidant and antibacterial activities of Cacalia hastata L. extracts. Methods: The aerial parts of Cacalia hastata L. had been studied. These parts were extracted with 40%, 70%, 95% ethanol (1:10) by the remaceration method. Thin layer chromatography (TLC) was used for the identification of constituents as phenolic compounds and flavonoids, their quantities were determined by spectrophotometric methods, precipitation reactions were used for the qualitative analysis of the tannin, while its quantitative determination was performed by the direct titration with potassium permanganate using indigo sulfonic acid as an indicator. The antioxidant activity of extracts was evaluated by the DPPH assay and the antibacterial activity by the Agar diffusion method, respectively. Results: Quantities of phenolic compounds in 40%, 70% and 95% extracts were determined as 4.87%, 4.92%, and 4.17%, respectively. Whereas, total flavonoids were as 4.61%, 5.1%, and 4.13%, respectively. The reaction with ferric ammonium slag presented dark green color, which indicated the presence of a condensable agent. Total tannins were 7.4% in the 40% extract, 5.1% in the 70% extract, and 3.04% in the 95% extract, respectively, by titration with the potassium permanganate. In addition, all 40%, 70% and 95% extracts showed moderate DPPH scavenging activity as IC50 =48.5μg/ mL, IC50 =74.8μg/mL, IC50 =51.2 μg/mL, respectively, comparad to rutin. The 40% and 70% extracts exhibited antibacterial activity against Bacillus subtillis with 3mm and 4mm inhibition zones, respectively. Conclusion: According to the results, the 70% ethanol extract of Cacalia hastata L. was more rich in biologically active products such as phenolic compounds, and flavonoids, and its extracts demonstrated antioxidant and antibacterial activities.